Genome-wide analysis of long non-coding RNA expression and function in colorectal cancer - Fangyuan Jing; Huicheng Jin; Yingying Mao; Yingjun Li; Ye Ding; Chunhong Fan; Kun Chen (Tumor Biology)
Long non-coding RNAs (lncRNAs) are widely transcribed in the genome, but their expression profile and roles in colorectal cancer are not well understood. The aim of this study was to investigate the long non-coding RNA expression profile in colorectal cancer and look for potential diagnostic biomarkers of colorectal cancer. Long non-coding RNA microarray was applied to investigate the global long non-coding RNA expression profile in colorectal cancer. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses were performed using standard enrichment computational methods. The expression levels of selected long non-coding RNAs were validated by quantitative reverse transcription polymerase chain reaction. The relationship between long non-coding RNA expression levels and clinicopathological characteristics of colorectal cancer patients was assessed. Coexpression analyses were carried out to find the coexpressed genes of differentially expressed long non-coding RNAs, followed by gene ontology analysis to predict the possible role of the selected long non-coding RNAs in colorectal carcinogenesis. In this study, a total of 1596 long non-coding RNA transcripts and 1866 messenger RNA transcripts were dysregulated in tumor tissues compared with paired normal tissues. The top upregulated long non-coding RNAs in tumor tissues were CCAT1, UCA1, RP5-881L22.5, NOS2P3, and BC005081 and the top downregulated long non-coding RNAs were AK055386, AC078941.1, RP4-800J21.3, RP11-628E19.3, and RP11-384P7.7. Long non-coding RNA UCA1 was significantly upregulated in colon cancer, and AK055386 was significantly downregulated in tumor with dimension <5 cm. Functional prediction analyses showed that both the long non-coding RNAs coexpress with cell cycle related messenger RNAs. The current long non-coding RNA study provided novel insights into expression profile in colorectal cancer and predicted the potential roles of long non-coding RNAs in colorectal carcinogenesis. Among the dysregulated long non-coding RNAs, UCA1 was found to be associated with anatomic site, and AK055386 was found associated with tumor size. Further functional investigations into the molecular mechanisms are warranted to clarify the role of long non-coding RNA in colorectal carcinogenesis.